2023
DOI: 10.5858/arpa.2022-0343-oa
|View full text |Cite
|
Sign up to set email alerts
|

Tumoral Intraductal Neoplasms of the Bile Ducts Comprise Morphologically and Genetically Distinct Entities

Abstract: Context.— Tumoral (grossly visible) intraductal neoplasms of the bile ducts are still being characterized. Objective.— To investigate their morphologic, immunohistochemical, and molecular features. Design.— Forty-one cases were classified as gastric-, intestinal-, pancreatobiliary-type intraductal papillary neoplasm (IPN), intraductal oncocytic papillary neop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 53 publications
0
19
0
Order By: Relevance
“…50 However, even the patients with invasive carcinoma appear to have a relatively protracted clinical course. 49,50 Recently, another classification system has been proposed to classify IPNBs as Types 1 and 2. 53 Type 1 IPNBs are most found in intrahepatic bile ducts and characterised with regular villous, papillary or tubular structures, usually with low-grade dysplasia.…”
Section: N T R a D U C T A L P A P I L L A R Y N E O P L A S M S O F ...mentioning
confidence: 99%
See 3 more Smart Citations
“…50 However, even the patients with invasive carcinoma appear to have a relatively protracted clinical course. 49,50 Recently, another classification system has been proposed to classify IPNBs as Types 1 and 2. 53 Type 1 IPNBs are most found in intrahepatic bile ducts and characterised with regular villous, papillary or tubular structures, usually with low-grade dysplasia.…”
Section: N T R a D U C T A L P A P I L L A R Y N E O P L A S M S O F ...mentioning
confidence: 99%
“…49,[59][60][61] Moreover, like their pancreatic counterparts, oncocytic-type IPNBs may reveal ATP1B1::PRKACB fusion and IPNBs with a tubular growth pattern have relatively few recurrent genetic aberrations. 49 Goeppert et al also reported that papillary and tubulopapillary/tubular neoplasms differ in their DNA methylation profiles. 58 These findings suggest that, just like the pancreatic ones, biliary IOPNs and ITPNs should be separated from the other mass-forming intraductal neoplasms of the bile ducts.…”
Section: N T R a D U C T A L P A P I L L A R Y N E O P L A S M S O F ...mentioning
confidence: 99%
See 2 more Smart Citations
“…When invasion is present, the term “IPNB with associated invasive carcinoma” is used. Although it has not been officially recognized as a distinct entity in the bile duct yet, emerging studies show that, as described in the pancreas, intraductal tubulopapillary neoplasm (ITPN) is another rare premalignant lesion that can also involve the bile ducts 6–8 . Histologically, ITPN is characterized by intraductal tubulopapillary growth.…”
Section: Introductionmentioning
confidence: 99%